ANTENA MIKROSTRIP DUAL BAND MONOPOLE RECTANGULAR RING UNTUK APLIKASI WLAN DAN WiMAX - Lili Ruhyana (Fakultas Teknik Universitas 17 Agustus 1945 Cirebon, 2019)
Antenna is one of important thing in the networking telecommunication system without the cable, diffirent of frequency range is need a tool of antenna which the different to that available with necessary of frequency is used. A problem has appear that needed a antenna dual band which can operate in the diffirent of frequency range. The research was made a design antene dual band microstrip monopole model with the rectangular ring shape in the patch part, adding the slot in square ring part and slot in the channel transmission, with the miniaturisasi antenna shape for the result of diffirent of frequency range which the diffirent between 3,4 GHz and 5,2 GHz so the antene could operated dual band and would been used for the network application WiMAX and WLAN. Design antenna was used material Roger Duroid 5880, substrate 36 mm x 26 mm, , Wg =26 mm, Lg=11 mm, W=22,5 mm, L=19 mm, width ring (a,b) = 3 mm, distance between side ring (c)=14 mm, distance between up and bottom ring (d)=16,5 mm, high channel transmision (Lf)=11,5 mm, width channel transmision (Wf)=3 mm, width slot channel transmision (sb)=1 mm, high slot channel transmision (sa)=8,5 mm, slot lenght s1= 6 mm, slot lenght s1q=3 mm, slot lenght s2=9,5 mm, slot lenght s2a=7,5 mm. Programming and simulation was used HFSS 13. The simulation used HFFS obtained antenna worked in the frequency was 3,4 GHz and 5,2 GHz, refelction factor was -32,97 dB and -18,12 dB, VSWR ≤ 2, bandwidth 5,88% and 3,84%. Result of measuring with used the Vector Network Annalyzer (VNA) ZVL 13 showed antenna worked in the frequency was 3,1 GHz and 4,7 GHz, refelction factor was -32,94 dB and -18,22 dB, VSWR ≤ 2, bandwidth 22,58% dan 8,51%.